PERAN KOPERASI WANITA (KOPWAN) DALAM RANGKA PEMBERDAYAAN EKONOMI MASYARAKAT PADA KAWASAN RAWAN BENCANA DI WILAYAH KABUPATEN MOJOKERTO - Fediyanty Agustinah (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2017)
This study uses research focus are 3 (three) names cooperatives located in the 3 (three) village, namely; 1) Women's Cooperative "Puan Jaya" in the village of Kepuhanyar, District Mojoanyar, 2) Women's Cooperative "Said Self" in the village of Sooko Sooko, and 3) Cooperative Women 'Rukun Makmur "in Jambuwok District Trowulan. Conditions that are cooperative efforts in disaster-prone areas in Mojokerto, in average running well and operating within the rules of the cooperative effort. But in terms of business scale of 1 (one) cooperative elected is still in business scale is relatively small and weak, so as to be able to play a role in the economic empowerment of exposure in disaster-prone areas, still need to be given assistance towards increasing the role of cooperatives, particularly in times the event of a disaster. Because when disaster strikes that hit the region in which the cooperative operates, can be expected impact of disasters will affect the infrastructure and business activities of cooperatives and the public economy cooperative members and communities other common, both in terms of production, volume of business, the availability of raw materials and household economy , Model of economic empowerment through Strengthening Business Facilitation Program Revolving Fund.